PENGGUNAAN METAFORA GURU DALAM WACANA KELAS ONLINE PEMBELAJARAN BAHASA INDONESIA DI MEDIA SOSIAL YOUTUBE - Fathanah Syamsuddin; Nurhusna Nurhusna (Fakultas Teknik Universitas Negeri Makassar, 2023)
The Use of Teacher Metaphors in Online Class Discourse on Indonesian Language Learning on Youtube and Social Media. This research uses a qualitative descriptive method and aims to examine the use of metaphorical types and functions in online class discourse on Indonesian language learning on YouTube and social media. The results of the study reveal that the types of teacher metaphors used in Indonesian language learning class discourse on YouTube and social media use anthropomorphic metaphors, animal metaphors, metaphors from concrete to abstract, and synesthetic metaphors. The functions of metaphors in learning Indonesian online on YouTube are information functions, expression functions, and directive functions. The most common type of metaphor found in this study is the synesthetic metaphor. The most common use of the metaphorical function found in this research is the information function.